Legal Instruments for Increasing Public Control Efficiency of Municipal Property Use of in the Context of Digitalization - Zarina K. Kondratenko; Anastasiya V. Kamaeva; Stanislav V. Pushkarev; Nikolai N. Smirnov; Nikita S. Vavilov (Communications of International Proceedings, 2021)
The article analyzes the regulatory legal acts of the Russian Federation that regulate public control over the use of municipal property. Various municipal programs focused on the use of municipal property are considered. The article shows “Smart City”, the project developed by the Mari State University. The purpose of this article is to form a comprehensive scientific understanding of legal instruments for increasing the efficiency of public control over the use of municipal property in the context of digitalization. The methodological basis of the study is a set of methods for the scientific cognition of social processes, circumstances and facts. The research is based on the methodological principles of objectivity, determinism, historicism, integrity, complexity, consistency, structure, functionality, hierarchy, pluralism of explanation and understanding of law and comparative studies. The work was carried out through the methods of dialectical materialism as a fundamental tool in humanitarian research. The use of such general scientific methods as analysis, synthesis, deduction and induction should be noted in the work. The research results were tested in the process of teaching and educational activities.
Keywords: “Smart City”; digital economy; municipal entity; digitalization; digital technologies; local government; municipal property; public control.